MODELING THE TRANSFORMATION OF PROGRAM PERSONNEL MANAGEMENT PROCESSES IN A MULTIPROJECT ENVIRONMENT - Dotsenko, N. V.; Lutsiv, Y. S. (Systems and Technologies, 2026)
The article is devoted to the study of the transformation of HR management processes of programs in a multi-project environment. The purpose of the study is to develop a model of the transformation of HR management processes of programs in a multi- project environment. The study is based on the use of the project and program approaches to managing program projects, the methodological support for business process reengineering, the combinatorial analysis and optimization methods. The scientific novelty is the development of a set of models of transformations of management processes: a contextual model and a decomposition model of the transformation of HR management processes of programs in a multi-project environment. The study yielded results that contribute to improving the effectiveness of transformation. An analysis of approaches to studying transformation processes identified aspects that should be considered when developing an adaptive digital HR ecosystem. The structure and functions of an adaptive digital HR architecture are defined. Typical characteristics of an adaptive digital HR architecture for a multi-project environment are identified, and their classification is proposed. To formalize transformations, the contextual model for transforming HR management processes for programs in a multi-project environment was developed. A decomposition of the transformation processes was performed, and a model for transforming HR management processes for programs in a multi-project environment was constructed. Elements of a multi-agent transformation system were identified, and information support for transformation was considered. The application of reengineering to manage transformation processes is considered. The main stages of transformation are identified. Using the proposed models will formalize transformation processes and identify the starting point for transformations. The created TO BE process models, a register of transformation changes, and transformation recommendations will provide information and methodological support for management decision-making.